Differential Patterns of the Division of Parenthood in Chinese Family: Association With Coparenting Behavior - Zou, Shengqi; Wu, Xinchun; Liu, Chang (Frontiers in Psychology, 2019)
We explored the division of parenthood in Chinese families with adolescents by identifying the parental involvement patterns in the data obtained from 786 pairs of parents. Division-of-parenthood patterns were created via factor mixture modeling using self-reported three dimensions of father and mother involvement. Three differential division-of-parenthood patterns were identified: (a) parent-cooperation pattern, where moderate and equivalent involvement existed between mothers and fathers; (b) mother-dominated pattern, where mother involvement was particularly greater than father involvement; and (c) father-dominated pattern, where father involvement was particularly greater than mother involvement. Families were more likely to be in the mother- or the father-dominated pattern as their levels of positive coparenting behaviors increased. By contrast, as the levels of paternal conflict behavior increased, families were likely to be in the mother-dominated pattern. This study highlighted parents’ individual parenting role, the diverse division-of-parenthood patterns in the family, and the important role of coparenting behavior.